VARIOUS FACTORS AFFECT THE QUALITY OF FERMENTED CASSAVA STARCH - Bambang Triwiyono; Abdurachman Abdurachman; Aton Yulianto (Politeknik Negeri Lampung., 2020)
Fermented cassava starch is one of modified cassava starch products and used in many countries in several food products. The fresh extracted cassava starch is modified by a process of fermentation and sun drying by means the traditional methods. Several works have shown that fermentative process alters the starch granule, giving fermented starch its characteristics are different from those of the native cassava starch. The main difference between fermented cassava starch and native starch reside in the expansion property. Understanding the transformation of physico-chemical properties of cassava starch during fermentation is important for controlling the production processes. This discourse refers to the several works that intend to chemically show the expansion property of fermented cassava starch, considered a chemically and enzymatically modified product, with acidic characteristics, perforated granules and high expansion capacity.Â Expansion is a natural characteristic of fermented cassava starch, defined as the growth rate of the dough during oven cooking, also referred to as expansion rate. The main aim of this discourse is to get a better understanding how to manage the production processes in order to achieve greater consistency in the quality of sour cassava starch.